Major primary bile salts repress Salmonella enterica serovar Typhimurium invasiveness partly via the efflux regulatory locus ramRA - Giraud, Etienne; Baucheron, Sylvie; Foubert, Isabelle; Doublet, Benoît; Nishino, Kunihiko; Cloeckaert, Axel (Frontiers in Microbiology, 2024)
We have previously reported the identification and characterization of the ramRA locus in efflux-mediated multidrug resistance, including antimicrobials and bile salts, of Salmonella enterica serovar Typhimurium (S. Typhimurium). This regulatory locus was also suggested to participate in intestinal cell invasion of S. Typhimurium. In the present study, we investigated the role of individual bile salts in this ramRA-mediated regulation of cell invasion. Our study identified chenodeoxycholate and its conjugated-derivative salts as main actors in repression of S. Typhimurium cell invasion, and this repression appeared partly dependent on the ramRA regulatory locus. We believe this study is of interest for the readers of Frontiers in Microbiology, and is more particularly in the scope of the section Infectious Agents and Disease. We wish our study to be considered in the Research Topic "Conference Research Topic: 9th Symposium on Antimicrobial Resistance in Animals and the Environment (ARAE 2023)", a conference that was organized by our research group.